Determination of short-term power dispatch schedule for a wind farm incorporated with dual-battery energy storage scheme - Yao, D.; Choi, San Shing; Tseng, K.; Lie, T. (The Institute of Electrical and Electronic Engineers (IEEE), 2012)
A battery energy storage scheme to enable short-term dispatch commitment from a grid-connected wind-turbine generating power station is considered. Among the various types of energy storage medium, technical factors leading to the selection of battery are explained. The scheme utilizes two battery energy storage systems (BESS) in which the generated wind power charges one BESS while concurrently, the second BESS is to discharge power into the grid. The role of the two BESS interchanges when the BESS reaches specified state of charge/discharge. Furthermore, based on forecasted charging wind power and the monitored states of charge of the two BESS, the discharge power level from the generating station is determined and scheduled a few hours ahead. The dispatch scheme maximizes wind energy harnessed, achieved with the minimum number of the BESS switch-overs. The design thus prolongs the service life of the BESS. Numerical examples to demonstrate the performance of the scheme are also included. © 2010 IEEE.